Early prognostic factors in septic shock cancer patients: a prospective study with a proteomic approach. Issue 4 (7th January 2018) - Mokart, D.; Saillard, C.; Zemmour, C.; Bisbal, M.; Sannini, A.; Chow‐Chine, L.; Brun, J.‐P.; Faucher, M.; Boher, J.‐M.; Toiron, Y.; Chabannon, C.; Borg, J.‐P.; et al.
Abstract : Background: Organ failures are the main prognostic factors in septic shock. The aim was to assess classical clinico‐biological parameters evaluating organ dysfunctions at intensive care unit admission, combined with proteomics, on day‐30 mortality in critically ill onco‐hematology patients admitted to the intensive care unit for septic shock. Methods: This was a prospective monocenter cohort study. Clinico‐biological parameters were collected at admission. Plasma proteomics analyses were performed, including protein profiling using isobaric Tag for Relative and Absolute Quantification (iTRAQ) and subsequent validation by ELISA. Results: Sixty consecutive patients were included. Day‐30 mortality was 47%. All required vasopressors, 32% mechanical ventilation, 33% non‐invasive ventilation and 13% renal‐replacement therapy. iTRAQ‐based proteomics identified von Willebrand factor as a protein of interest. Multivariate analysis identified four factors independently associated with day‐30 mortality: positive fluid balance in the first 24 h (odds ratio = 1.06, 95% CI = 1.01–1.12, P = 0.02), severe acute respiratory failure (odds ratio = 6.14, 95% CI = 1.04–36.15, P = 0.04), von Willebrand factor plasma level > 439 ng/ml (odds ratio = 9.7, 95% CI = 1.52–61.98, P = 0.02), and bacteremia (odds ratio = 6.98, 95% CI = 1.17–41.6, P = 0.03). Conclusion: Endothelial dysfunction, revealed by proteomics, appears as an independent prognostic factor on day‐30 mortality, as well as hydric balance, acute respiratory failure and bacteremia, in critically ill cancer patients admitted to the intensive care unit. Endothelial failure is underestimated in clinical practice and represents an innovative therapeutic target.